(untitled) (Journal of Geography and Environmental Management, 2024)
The introduction of satellite technologies for determining coordinates opens up new opportunities both for creating a geodetic basis for the development of the subsoil, and for the production of surveying and geodetic works at mines. In this regard, it seems very promising to transfer the coordinates obtained by an automated method on the surface of an ellipsoid to a horizontal local projection oriented normally to a vertical line. At the same time, it is possible to control this deviation and select a local area that meets the specified accuracy parameters. Such an approach to the creation of a geodynamic polygon (GDP) during the development of the subsoil will certainly make it possible to more accurately make design decisions in kind. The article proposes an up-to-date approach to the formation of a geodynamic polygon, which consists in the use of a local flat surface with topocentric coordinates. The GDP created in topocentric coordinates has minimal distortions relative to geocentric coordinates, in which the lion’s share of geodetic work is carried out today. Calculations and concrete examples of the translation of coordinates from a geocentric system to a topocentric one (a flat projection of geocentric coordinates with topocentric coordinates) are given, in which the measurement results are equalized. It is important to note that the results are compared with respect to the Gauss-Kruger zonal coordinate system. The possibility of translating coordinates from one system to another is demonstrated in order to preserve traditional forms of material presentation and measurement evaluation.